Imaging in Pancreatic Neuroendocrine Tumors - Kapur, Savinay; Sharma, Raju; Goyal, Ankur (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Pancreatic neuroendocrine tumors (NETs) form a discrete subgroup of pancreatic neoplasms. They are rarer than pancreatic adenocarcinomas but need to be differentiated from other pancreatic tumors and pathologies as they carry a better prognosis. Imaging plays a central role in detecting, characterizing, and staging of pancreatic NETs as they tend to have typical radiological features. A lot of advancements have taken place in the field of imaging and theranostics which have revolutionized their detection and management. In this article we shall review the various imaging techniques available to the radiologist, salient imaging features of different types of pancreatic NETs, staging and grading systems, as well as a brief overview of their management.
Keywords: computed tomography; imaging; magnetic resonance imaging; neuroendocrine tumors; pancreas; pancreatic malignancies